Gambaran Regulasi Emosi Remaja Korban Bullying di Pondok Pesantren Nasyrul Ulum, Kabupaten Sumenep - Adisty Nur Fauziyyah; Arsi Galuh Prameswari Wibowo; Netty Herawati (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This research discusses the description of emotional regulation in adolescent victims of bullying at the Nasyrul Ulum Aengdake Islamic Boarding School, Bluto District, Sumenep Regency. Adolescence, as a transitional phase, is often characterized by emotional tension which can trigger delinquent behavior, including bullying. Bullying, as an act of violence, can have serious impacts on victims, including physical injuries and negative effects on concentration and learning patterns. This research began with community service activities aimed at increasing self-resilience and psychological empowerment of teenagers as an effort to overcome bullying. The data collection method in this research was through Focus Group Discussion (FGD). The results of this research explain that bullying that occurs at the Nasyrul Ulum Islamic Boarding School takes various forms, such as teasing, insulting, and even physical violence. The impacts are also varied. Teenagers have their own way of dealing with the negative emotions they are feeling so that the problems they are facing can gradually disappear.